Changes of metabolic parameters, antioxidant capacity, and gut microbiota in response to substitution of ferrous sulfate with iron hydroxy methionine analog chelate in weaned piglets - Fu, Yuemeng; Zhou, Guohui; Liu, Yuhang; Yuan, Xuejun; Jiao, Ning; Lu, Wenbiao; Yang, Weiren (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPrevious studies have suggested that dietary organic iron offers health advantages compared to its inorganic counterpart. However, the effects of iron hydroxy methionine analog chelate (Fe-HMA) supplementation in weaned piglets have not been fully explored. Therefore, this study aimed to investigate the effects of replacing ferrous sulfate with Fe-HMA as the iron source on serum biochemistry, antioxidant capacity, and gut microbiota in weaned piglets.MethodsOne hundred and twenty weaned piglets were randomly allocated to two treatment groups. Each group contained four replicates, with 15 pigs per replicate. Piglets were fed either 100 mg Fe/kg in the form of ferrous sulfate (Fe-sulfate group) or 50 mg Fe/kg in the form of Fe-HMA (Fe-HMA group) as the iron source for 28 days.Results and discussionResults showed that supplementing Fe-HMA as an iron source significantly increased the levels of triglycerides and glucose in portal venous serum, albumin in both serum and portal venous serum and decreased serum low-density lipoprotein level in weaned piglets. Additionally, Fe-HMA supplementation significantly reduced serum and liver malondialdehyde levels, while increasing catalase (CAT), glutathione peroxidase (GSH-Px), total superoxide dismutase, and manganese superoxide dismutase levels in serum, as well as GSH-Px and CAT levels in the liver. Moreover, Fe-HMA regulated the intestinal microbiota composition, notably increasing the relative abundance of Proteobacteria and decreasing microbes involved in aromatic_compound_degradation. In conclusion, dietary replacing inorganic iron with Fe-HMA improved metabolic parameters and antioxidant capacity, and regulated gut microbiota composition in weaned piglets.